A Divergent P Element and Its Associated MITE, BuT5, Generate Chromosomal Inversions and Are Widespread within the Drosophila repleta Species Group - Rius, Nuria (Oxford University Press, 2013)
The transposon BuT5 caused two chromosomal inversions fixed in two Drosophila species of the repleta group, D. mojavensis and D. uniseta. BuT5 copies are approximately 1-kb long, lack any coding capacity, and do not resemble any other transposable element (TE). Because of its elusive features, BuT5 has remained unclassified to date. To fully characterize BuT5, we carried out bioinformatic similarity searches in available sequenced genomes, including 21 Drosophila species. Significant hits were only recovered for D. mojavensis genome, where 48 copies were retrieved, 22 of them approximately 1-kb long. Polymerase chain reaction (PCR) and dot blot analyses on 54 Drosophila species showed that BuT5 is homogeneous in size and has a widespread distribution within the repleta group. Thus, BuT5 can be considered as a miniature inverted-repeat TE. A detailed analysis of the BuT5 hits in D. mojavensis revealed three partial copies of a transposon with ends very similar to BuT5 and a P-element-like transposase-encoding region in between. A putatively autonomous copy of this P element was isolated by PCR from D. buzzatii. This copy is 3,386-bp long and possesses a seven-exon gene coding for an 822-aa transposase. Exon–intron boundaries were confirmed by reverse transcriptase-PCR experiments. A phylogenetic tree built with insect P superfamily transposases showed that the D. buzzatii P element belongs to an early diverging lineage within the P-element family. This divergent P element is likely the master transposon mobilizing BuT5. The BuT5/P element partnership probably dates back approximately 16 Ma and is the ultimate responsible for the generation of the two chromosomal inversions in the Drosophila repleta species group.